A educação popular na formação de trabalhadores da economia solidária: avanços políticos e desafios pedagógicos - Adriane Vieira Ferrarini; Telmo Adams (Ciências Sociais Unisinos)
The article is a result of a research on how the principles and methods of the popular education – a consensus within the established discourse – are expressed in training practices in the solidarity economy in Rio Grande do Sul. The empirical research was conducted through interviews with agents from four representative entities of training and participant observation, sociopoetics and interviews with workers who participated in the Solidarity Economy Training Centre of South Brazil, a public policy implemented by Unisinos in the period of 2009-2012. The results showed political advances but also challenges to the democratic exercise of popular education, which requires a break with the hierarchy of knowledge and roles amid traditional contexts, procedures and instruments. These challenges are expressed through concrete conditions (insufficient resources and edicts that delimit deadlines and content – despite being a citizen achievement) and subjective (different conceptions of solidarity economy that trigger various methodological training options and conservative political-pedagogical legacies). Proposals revolved around increased participation of workers in training and easing of the edicts. The contradictions only confirmed that popular education is a process that challenges all people involved, with the utopia of building more democratic and supportive ways of producing and living as a point in common and unifying ideal. There is no formula or recipes in popular education, but constructed responses in ongoing dialogue across differences in dealing with contradictions and recreating practices and structures.